2015
DOI: 10.1093/jac/dkv042
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of the role of bacterial Hfq-interacting sRNAs in the response to antibiotics

Abstract: Our data indicate that Hfq-associated sRNAs potentially enable bacteria to adapt to antibiotic challenges via multifaceted approaches. Therefore, sRNA-based applications will form a new antibiotic arsenal for combating the rise in antibiotic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 47 publications
3
51
0
Order By: Relevance
“…Conversely, over-expression of SdsR renders E. coli cells more susceptible to levofloxacin and several other antibiotics (90,91). Repression of the tolC mRNA (Figure 3D), encoding part of a large multiple drug efflux pump (92), by SdsR is a key factor for this phenotype, however, regulation of additional target genes seems to matter as well (91).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, over-expression of SdsR renders E. coli cells more susceptible to levofloxacin and several other antibiotics (90,91). Repression of the tolC mRNA (Figure 3D), encoding part of a large multiple drug efflux pump (92), by SdsR is a key factor for this phenotype, however, regulation of additional target genes seems to matter as well (91).…”
Section: Discussionmentioning
confidence: 99%
“…TolC was also identified as one of a large number of targets of SdsR in Salmonella, using microarray analysis (K. S. Fröhlich, K. Haneke, K. Papenfort, and J. Vogel, personal communication). In another study published while the current work was being prepared for publication, the same plasmid library as that used here was screened for effects on sensitivity or resistance to a panel of antibiotics, and the overexpression of SdsR was found to increase sensitivity to multiple antibiotics, in particular, quinolones (29). Based on that observation and target prediction, the authors predicted tolC as a possible target, and a decrease in tolC mRNA was confirmed by reverse transcription-quantitative PCR (qRT-PCR) analysis after overexpression of the sRNA (29).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact functions of SdsR remain unclear, previous studies have suggested it has a role in modulating susceptibility to quinolone antibiotics. The overexpression of SdsR reduced resistance to quinolone antibiotics, such as levofloxacin, nalidixic acid, and norfloxacin, in multiple-drug-resistant strains of E. coli and Salmonella (29). In addition, SdsR was reported to contribute to an increase in the mutagenesis rate in E. coli cells treated with subinhibitory levels of ampicillin, presumably via its interaction with mutS (30).…”
mentioning
confidence: 99%
“…As it has been proposed before (Gruber and Sperandio 2015;Kim et al 2015;Peng et al 2015), computational analysis of the sRNAs' targets is an excellent starting point toward understanding their physiological roles in the cell. Here, we used TargetRNA2 as a target predictor for being the algorithm with the best correlation of targets predicted and actually confirmed, among the programs widely used for this purpose (Kery et al 2014).…”
Section: Discussionmentioning
confidence: 99%